Analisis Kebijakan Penguatan Keagamaan Mahasiswa Baru: Studi Kasus di Universitas Sains Al-Qur'an Wonosobo. - Saputra, Gondo Adhi; Yasyada, Ahmadan Haquridha (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2025)
This study aims to analyze the policy of strengthening religious values for new students at the Al- Qur'an Science University (UNSIQ) Wonosobo. The research uses a qualitative approach with a field research design to explore the religious strengthening program at UNSIQ. The results of the study show that UNSIQ has implemented a religious strengthening policy aimed at creating an academically excellent environment grounded in religious values. This policy is driven by the need to strengthen students' spiritual character, create a harmonious campus atmosphere, and foster religious awareness. Various activities have been carried out, such as Aswaja training, yellow book studies, worship practices, Mabit (night study), and the obligation to memorize Juz 30 of the Qur'an. Factors supporting the success of this policy include good time management, comprehensive socialization, programs integrated with the curriculum, the availability of platforms for student aspirations, comprehensive policy evaluation, and building interpersonal relationships with relevant parties. Although there are some challenges, UNSIQ remains committed to strengthening the religious dimension of new students as an integral part of the institution's vision and mission.